KEPUTUSAN RAPAT UMUM ANGGOTA (RUA) SEBAGAI DASAR PENETAPAN HONORARIUM PENGURUS PERHIMPUNAN PEMILIK DAN PENGHUNI SATUAN RUMAH SUSUN (PPPSRS) - Vicky Prayitno S; Saidil Adri (Bajang Institute, 2026)
The Association of Unit Owners and Residents of Condominiums (PPPSRS) is a legal entity established under Law Number 20 of 2011 concerning Condominiums, serving as a vehicle for unit owners and residents to manage common interests, including shared property, common areas, and common land. In practice, legal issues frequently arise concerning the validity of granting honorariums to the PPPSRS Management Board, given that such positions are essentially voluntary. This study analyzes the position of decisions made by the General Members' Meeting (RUA) as the legal basis for granting honorariums to the PPPSRS Management Board, using Organ Theory as an analytical framework within the law of legal entities. This research employs a normative legal method with statutory and conceptual approaches. The findings indicate that, based on Organ Theory, PPPSRS as a legal entity can only act through its organs, namely the RUA as the highest organ, the Management Board as the executive organ, and the Supervisory Board as the oversight organ. The RUA holds attributive authority to determine the association's financial policies, including the amount of the Management Board's honorarium, as a consequence of its position as the highest organ representing the collective will of all members.